2011
DOI: 10.1177/0898010111423420
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Expressions of African Americans and Whites in Cancer Pain

Abstract: Background Spiritual practices are one way that individuals cope with cancer pain. Purpose Describe and contrast expressions and values about the use of spirituality for pain in African American (AA) and White (WH) oncology patients. Methods Six groups (3 AA; 3 WH; n=42; mean age 58) were conducted. Focus group and qualitative methodology with a cultural interpretive lens was utilized. The Model of Integrated Spirituality provided the conceptual framework for understanding the narratives. Findings AAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
2
23
1
Order By: Relevance
“…These results indicated that spirituality appears to be a protective factor against patients' pain and symptom burdens and therefore heighten patients' QOL. Although previous studies have highlighted how spirituality is used as a coping skill either for cancer pain management or for the improvement of QOL, 44,45 the present study found that pain interference, symptoms, and spiritual well-being are primary contributors to the variance of overall QOL. Spiritual well-being also showed strong predictions of QOL social, emotional, and functional domains.…”
Section: Discussioncontrasting
confidence: 53%
“…These results indicated that spirituality appears to be a protective factor against patients' pain and symptom burdens and therefore heighten patients' QOL. Although previous studies have highlighted how spirituality is used as a coping skill either for cancer pain management or for the improvement of QOL, 44,45 the present study found that pain interference, symptoms, and spiritual well-being are primary contributors to the variance of overall QOL. Spiritual well-being also showed strong predictions of QOL social, emotional, and functional domains.…”
Section: Discussioncontrasting
confidence: 53%
“…Many authors on spirituality have referred to transcendence as a dimension of spirituality (Albaugh, ; Banks‐Wallace & Parks, ; Barker & Floersch, ; Barney & Buckingham, ; Bradley, ; Buck, ; Buck & Meghani, ; Chiu et al., ; Coyle, ; Crossley & Salter, ; Daly, ; Delgado, ; Gall et al., ; Griffith et al., ; Hodge & McGrew, ; Lowry, ; McSherry & Jamieson, ; Markani, Yaghmaei, & Fard, ; Miner‐Williams, ; Molzahn et al., ; Morrison‐Orton, ; Newlin et al., ; Oh & Kang, ; Papathanassoglou & Patiraki, ; Penman, Oliver, & Harrington, ; Pesut, ; Rican, ; Rich & Cinamon, ; Tanyi, ; Van Dover & Pfeiffer, ; Walton, ; Woodgate & Degner, ). Self‐transcendence has been defined as the ability to see beyond the boundaries of the self, the environment, and present limitations (Reed, ).…”
Section: Resultsmentioning
confidence: 99%
“…The third attribute that has been consistently referred to in the spirituality literature is meaning in life (Albaugh, ; Barker & Floersch, ; Buck, ; Buck & Meghani, ; Chiu et al., ; Coyle, ; Crossley & Salter, ; Daly, ; Delgado, ; Gall et al, ; Kunsongkeit & McCubbin, ; McSherry & Jamieson, ; Miner‐Williams, ; Molzahn et al., ; Morrison‐Orton, ; Mount, Lawlor, & Cassell, ; Newlin et al., ; Oh & Kang, ; Papathanassoglou & Patiraki, ; Pesut, ; Rican, ; Rich & Cinamon, ; Sessanna et al., ; Tanyi, ; Van Dover & Pfeiffer, ; Walton, ; Walton & Sullivan, ; Williams, ; Woodgate & Degner, ). This attribute of spirituality is exemplified in a study by Walton and Sullivan (), in which one man with prostate cancer said: “Having prostate cancer has certainly enhanced my understanding of my mortality … it just makes me appreciate all the more the life that I have” (p. 143).…”
Section: Resultsmentioning
confidence: 99%
“…Despite catastrophization, African Americans often are able to find a blessing even in the midst of pain. 1 They may even give the pain over to God. 34 Consequently, the health care team may misinterpret these actions as fatalistic thinking, maladaptive coping, or peripheral self-care, when, in fact, it is a form of spiritual acceptance of a physical condition and a way to relinquish control to a higher power.…”
Section: Painmentioning
confidence: 99%